(untitled) (CR. Conservación y Restauración, 2025)
This work provides details on the entry of 176 archaeological objects into the ethnological and archaeological warehouses of the old Museo Nacional de las Culturas (Mexico). These pieces are of different proportions and materials, their origin is the state of Guerrero, and were classified as representative of the so-called western culture. The collection was donated by the couple of international artists Elizabeth Taylor and Richard Burton. The temporal context of this event is dark and suggestive because it was dominated by the trafficking and illegal sale of national heritage. In this way, more than a story, this work illustrates how the national laws were consolidated for guiding the actions of those who are usually involved, at different times, in circumstances that refer to archaeological looting, traffic and archaeological illegal trade. The fact was documented with some of the files of the Historical Archive of the current Museo Nacional de las Culturas del Mundo, which constitutes a sample of how the maintenance of this type of space transcends.